Ransomware revealed : a beginner's guide to protecting and recovering from ransomware attacks - Hassan, Nihad A. (Apress, 2019)
Know how to mitigate and handle ransomware attacks via the essential cybersecurity training in this book so you can stop attacks before they happen. Learn the types of ransomware, distribution methods, internal structure, families (variants), defense strategies, recovery methods, and legal issues related to reporting ransomware incidents to authorities and other affected parties. This book also teaches you how to develop a ransomware incident response plan to minimize ransomware damage and recover normal operations quickly. Ransomware is a category of malware that can encrypt your computer and mobile device files until you pay a ransom to unlock them. Ransomware attacks are considered the most prevalent cybersecurity threats today-the number of new ransomware variants has grown 30-fold since 2015 and they currently account for roughly 40% of all spam messages. Attacks have increased in occurrence from one every 40 seconds to one every 14 seconds. Government and private corporations are targets. Despite the security controls set by organizations to protect their digital assets, ransomware is still dominating the world of security and will continue to do so in the future. Ransomware Revealed discusses the steps to follow if a ransomware infection occurs, such as how to pay the ransom through anonymous payment methods, perform a backup and restore your affected files, and search online to find a decryption tool to unlock (decrypt) your files for free. Mitigation steps are discussed in depth for both endpoint devices and network systems. You will: Be aware of how ransomware infects your system Comprehend ransomware components in simple terms Recognize the different types of ransomware families Identify the attack vectors employed by ransomware to infect computer systems Know how to prevent ransomware attacks from successfully comprising your system and network (i.e., mitigation strategies) Know what to do if a successful ransomware infection takes place Understand how to pay the ransom as well as the pros and cons of paying Set up a ransomware response plan to recover from such attacks.